The secret language of business : - Hogan, Kevin (John Wiley & Sons, 2008)
The Secret Language of Business reveals the secrets of body language and nonverbal communication. Successful professionals need more than just good communication skills, you also need the ability to interpret the nonverbal signals that everyone displays. You’ll learn how to master and manipulate your own body language, read the body language of others, and influence people through your new skills and perception. No matter what business you’re in, this is a valuable guide to achieving more in life and business.